Exploring TESOL Teachers’ Perceptions of Project-Based Assessment in ELT Classroom - Izzah, Navisatul (International Journal of Language Education, 2021)
This study explored the perceptions of TESOL teachers in Indonesia regarding the use of project-based assessment in their classrooms. As assessment has undergone massive development and shifting paradigms, there has been recognition for teachers to reconceptualise their assessment practice. There have been attempts made by some countries, including Indonesia, to introduce various assessment methods including project-based assessment. Since it has been introduced in Indonesia in 2016 through government document, little is known about TESOL teachers’ use of this assessment method. Furthermore, project-based assessment has mostly been used in science classroom, but not in ELT classroom. Research study regarding the use of project-based assessment in ELT classroom and how TESOL teachers in Indonesia perceive the use of project-based assessment would therefore be valuable additions to the field. This study used a qualitative case study as its methodology to gain an in-depth understanding of the emerging issue. Four ELT teachers around Surabaya were interviewed about their project-based assessment practice. The findings of this study revealed that teachers highly value the use of project-based assessment in their classroom despite the challenges they encounter. Hence, some implications and directions for further studies are also provided.Keywords: assessment method, classroom assessment, TESOL Teachers, project-based assessment, ELT in Indonesia.